2018
DOI: 10.1016/j.sedgeo.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic influence of Mt. Fuji on the watershed of Lake Motosu and its impact on the lacustrine sedimentary record

Abstract: Lacustrine sediments are particularly sensitive to modifications within the lake catchment. In a volcanic area, sedimentation rates are directly affected by the history of the volcano and its eruptions. Here, we investigate the impact of Mt. Fuji Volcano (Japan) on Lake Motosu and its watershed. The lacustrine infill is studied by combining seismic reflection profiles and sediment cores. We show evidence of changes in sedimentation patterns during the depositional history of Lake Motosu. The frequency of large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Geochemistry of glass shards from MOT15-2 (red, this study). A and B) K 2 O versus TiO 2 and K 2 O versus SiO 2 for the 1.915-mcd pumice compared to data from shards collected proximal to the Kawagodaira (Kg) caldera (blue, this study), shards from Site MOT15-1 (orange, Lamair et al, 2018), and from Lake Suigetsu (black, McLean et al, 2018). C and D) The same for the 3.455-mcd pumice (red, this study) compared to proximal shards from the Kikai-Akahoya (K-Ah) eruption (blue, this study; gray, Smith et al, 2013;cyan, Machida and Arai, 2003) and distal shards subsampled from Lake Suigetsu sediment cores (black, Smith et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Geochemistry of glass shards from MOT15-2 (red, this study). A and B) K 2 O versus TiO 2 and K 2 O versus SiO 2 for the 1.915-mcd pumice compared to data from shards collected proximal to the Kawagodaira (Kg) caldera (blue, this study), shards from Site MOT15-1 (orange, Lamair et al, 2018), and from Lake Suigetsu (black, McLean et al, 2018). C and D) The same for the 3.455-mcd pumice (red, this study) compared to proximal shards from the Kikai-Akahoya (K-Ah) eruption (blue, this study; gray, Smith et al, 2013;cyan, Machida and Arai, 2003) and distal shards subsampled from Lake Suigetsu sediment cores (black, Smith et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…10). However, Lamair et al (2018) geochemically analyzed scoria deposited in Lake Motosu and interpreted that it is sourced from Mt. Fuji.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of (finely) laminated sediments that exhibit marked color variations, visual core correlation can be achieved down to millimeter-scale accuracy (Figure 11A,B; [18,23,39,86]). Alternatively, (near-)continuous scanning or logging data, such as XRF, magnetic susceptibility, or X-ray computed tomography (CT), can be used to correlate gradual or abrupt variations through time of the background sediments (Figure 11C [19,102,174]). Additionally, independent (varve-counted) age models for each single core have allowed the correlation of cores within a lake basin [175].…”
Section: Core Correlationmentioning
confidence: 99%
“…Previous studies collected sediment cores from Lake Motosu to study past environmental changes in the region (Lamair et al, 2018(Lamair et al, , 2019Obrochta et al, 2018). Obrochta et al (2018) measured radiocarbon in TOC from sediments, and they reported a D 14 C surface value of D 14 C of -41 + 2.5‰.…”
Section: Implications For Reservoir Ages Of Lake Motosu and Lake Kawaguchimentioning
confidence: 99%